Pelatihan Membuat Soal Tes Hasil Belajar Berbasis High Order Thinking Skill untuk Guru SMA-SMP Sederajat di Kabupaten Rokan Hilir Provinsi Riau - Asyrul Fikri; Ahmal Ahmal; Yanuar Al Fiqri; Nurdiansyah Nurdiansyah (Jurnal Pengabdian UNDIKMA, 2021)
The purpose of this activity is to give an ability for the Teacher of Middle and High Schools in Kecamatan Tanah Putih, Riau Province to understand and be able to apply the HOTS evaluation method at their respective schools and students. The methods used are lectures, questions and answers, trials/simulations, and workshop. The results of this training activity that has been carried out, it can be concluded that the objectives of the activity have been successfully achieved. This is evidenced by the excellent enthusiasm of the trainees during the discussion process and the results of the assignments given to the presenters to the trainees, indicating an increase in the understanding and ability of teachers to integrate HOTS into learning outcomes test instrument.